2017
DOI: 10.1094/phyto-09-16-0322-r
|View full text |Cite
|
Sign up to set email alerts
|

Potato virus Y Transmission Efficiency from Potato Infected with Single or Multiple Virus Strains

Abstract: There has been a recent shift in the prevalence of Potato virus Y (PVY) strains affecting potato with the ordinary strain PVY declining and the recombinant strains PVY and PVY emerging in the United States. Multiple PVY strains are commonly found in potato fields and even in individual plants. Factors contributing to the emergence of the recombinant strains are not well defined but differential aphid transmission of strains from single and mixed infections may play a role. We found that the transmission effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Transmission efficiency for PVY N and PVY N-Wi was shown not to differ in a previous study [ 34 ], which is consistent with the N e values estimated for this two strains in our study. Even though some studies demonstrated different efficiency of transmission for different PVY strains [ 35 ], conclusions between different studies are not consistent [ 36 ] and can be influenced by, e . g ., potato cultivar, viral titer in the source leaf [ 37 , 38 ], virus strain, virus isolate, aphid species and clonal populations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transmission efficiency for PVY N and PVY N-Wi was shown not to differ in a previous study [ 34 ], which is consistent with the N e values estimated for this two strains in our study. Even though some studies demonstrated different efficiency of transmission for different PVY strains [ 35 ], conclusions between different studies are not consistent [ 36 ] and can be influenced by, e . g ., potato cultivar, viral titer in the source leaf [ 37 , 38 ], virus strain, virus isolate, aphid species and clonal populations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…‘Red Maria’ potato seedlings grown from true seed were used as recipient plants in all transmission assays. This method was adopted from previous studies [5, 10] and is an efficient and easy way to generate large numbers of similar sized seedlings that do not differ in susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…The green peach aphids ( Myzus persicae ) used in this study were previously described [10, 25] and maintained on ‘Purple Top White Globe’ turnip ( Brassica rapa subsp rapa ) plants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Green peach aphids (Myzus persicae) were reared on 'Purple Top White Globe' turnip (Brassica rapa subsp rapa) as previously described [62,63]. Apterous third and fourth instar aphids were collected and starved for 1-2 h before being placed on the abaxial surface of a young, fully expanded, detached tobacco or potato leaf systemically infected with different individual PVY strains or mixtures of strains and allowed a 2-3 min acquisition access period (AAP).…”
Section: Plant and Aphid Samplesmentioning
confidence: 99%